First sound velocity in liquid ⁴He - Hryhorchak, O.I. (Condensed Matter Physics, 2015)
Based on the many-boson system structure factor, which takes into account three- and four-particle direct correlations, there was found the first sound velocity temperature behaviour in liquid ⁴He in the post-RPA approximation. The expression received for the sound velocity matches with the well-known results in both low and high temperature limits. The results of this paper can be used to analyze the contributions of three- and four-particle correlations into thermodynamic and structural features of liquid ⁴He . На основi виразу для структурного фактора багатобозонної системи з урахуванням прямих три- i чотиричастинкових кореляцiй знайдено температурну поведiнку швидкостi першого звуку в рiдкому ⁴He в
пост-RPA наближеннi. У границi як низьких, так i високих температур отриманий вираз переходить у вже
вiдомий. Результати можуть бути застосованi для аналiзу внескiв три- та чотиричастинкових кореляцiй у
термодинамiчнi та структурнi функцiї рiдкого ⁴He.